Respons strategis Myanmar terhadap Cina: Analisis hedging 2014-2018 - Simangunsong, Rahayu (Institute for Advanced Science Social, and Sustainable Future, 2024)
Myanmar as a small power in the Southeast Asian region requires strategy to maintain its existence. This article discussed Myanmar's strategic response to one of the rising powers in the region, namely China. The hedging framework (Kuik, 2016) is used to examine the tendency of Myanmar's strategic response to China. Hedging is defined as behavior to seek assurance in situations with high levels of uncertainty. Myanmar's relations towards China does not explicitly indicate pure balancing or bandwagoning. Despite its dependency to China, mainly in the economy and military aspect, Myanmar still cooperates with other big power countries. Myanmar hedges against China to maximize profits and reduce the possibility of risk. Myanmar's tendency to depend on China is inseparable from the lack of options available. Sanctions imposed by the international community on the Rohingya issue have implications for the reduction of countries willing to cooperate with Myanmar.